Androgen Excess Produces Systemic Oxidative Stress and Predisposes to β-Cell Failure in Female Mice - Liu, Suhuan (Public Library of Science, 2010)
In women, excess production of the male hormone, testosterone (T), is accompanied by insulin resistance. However, hyperandrogenemia is also associated with β-cell dysfunction and type 2 diabetes raising the possibility that androgen receptor (AR) activation predisposes to β-cell failure. Here, we tested the hypothesis that excess AR activation produces systemic oxidative stress thereby contributing to β-cell failure. We used normal female mice (CF) and mice with androgen resistance by testicular feminization (Tfm). These mice were exposed to androgen excess and a β-cell stress induced by streptozotocin (STZ). We find that following exposure to T, or the selective AR-agonist dehydrotestosterone (DHT), CF mice challenged with STZ, which are normally protected, are prone to β-cell failure and insulin-deficient diabetes. Conversely, T-induced predisposition to β-cell failure is abolished in Tfm mice. We do not observe any proapoptotic effect of DHT alone or in the presence of H(2)O(2) in cultured mouse and human islets. However, we observe that exposure of CF mice to T or DHT provokes systemic oxidative stress, which is eliminated in Tfm mice. This work has significance for hyperandrogenic women; excess activation of AR by testosterone may provoke systemic oxidative stress. In the presence of a prior β-cell stress, this may predispose to β-cell failure.